QUALITY CONTROL OF THE HERBAL DRUG JUSTICIA PECTORALIS JACQ. (ACANTHACEAE) AS AN ADVANCE IN CLINICAL PHYTOTHERAPY (CIPEEX, 2025)
Introduction: The Cerrado presents a rich biodiversity of medicinal flora, and the use of medicinal plants as a popular tradition passed down through generations still persists in society. Among the various plant families in this biome, the Acanthaceae family stands out, comprising about 275 genera and 4,000 species. This family includes several species with great pharmacological potential. Within Acanthaceae, the genus Justicia is the largest and is popularly used, characterized mainly by the presence of alkaloids, lignans, flavonoids, and terpenoids, compounds responsible for its pharmacological potential. Objective: To perform the quality control of the herbal drug Justicia pectoralis Jacq. (Acanthaceae). Method: This is an experimental study conducted through the extraction, qualification, and quantification of the chemical constituents of the essential oil and the phytochemical screening of the species. Results: The presence of saponins and coumarins was observed, along with traces of flavonoid and cardioactive glycosides. The morpho-anatomical analysis showed similarity with other members of the Acanthaceae family. Conclusion: The analysis demonstrated the presence of several compounds that suggest the pharmacological activity of the plant.
Keywords: Phytochemistry; Essential oil; Justicia